Regression Analysis Approach for Mathematical Model Development in Dynamic System. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We proposed an approach using multiple regression analysis to develop a mathematical model that represents a dynamic manufacturing system. Simulation data are specifically analyzed using this multiple regression analysis approach to obtain a data pattern. The aim of the approach is to reduce the gap between theory and real-time data of the system. To evaluate the effectiveness of the proposed mathematical mode, simulation model was first validated using real-time data. The applicability of the proposed mathematical model was evaluated by testing with real-time data. The outcome +positively demonstrated that the develop mathematical model based on multiple regression analysis approach can be used to make predictions in the dynamic manufacturing environment with an acceptable error percentage range. The mathematical development in this field will enhance the future establishment of a decision-making model using a spreadsheet in the management field.